Teknik Art Therapy “Membatik” Untuk Meningkatkan Kecerdasan Emosional Peserta Didik Sekolah Menengah Pertama - Rahmiawan, Natasya Artamefilla; Khusumadewi, Ari; Purwoko, Budi; Winingsih, Evi (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2024)
Adolescence is characterized by emotional instability, which often leads to low emotional intelligence in individuals. This study aims to evaluate the effectiveness of art therapy techniques in improving adolescents' emotional intelligence. Using the Systematic Literature Review (SLR) method, journal searches were conducted online with the keywords "art therapy techniques and emotional intelligence," resulting in 8 selected journals published between 2017 and 2024 through Google Scholar. The findings indicate that art therapy, particularly the technique of batik-making, is effective in helping adolescents express their emotions through free patterns drawn on fabric while fostering precision and patience. In addition to enhancing emotional control and understanding, batik-making broadens adolescents' awareness of the importance of preserving traditional culture in the era of globalization. This study provides a foundation for further research on the potential of art therapy, especially batik-making, which remains underexplored in previous studies.